Is Mediastinoscopy Still the Gold Standard to Evaluate Mediastinal Lymph Nodes in Patients with Non-Small Cell Lung Carcinoma? - Sivrikoz, C. M.; Ak, I.; Simsek, F. S.; Döner, E.; Dündar, E. (The Thoracic and Cardiovascular Surgeon, 2012)
Objectives In this study, we aimed to define the efficacy of F-18 FDG PET/CT for the detection of mediastinal lymph node metastases by comparing the mediastinal findings of F-18 FDG PET/CT with the histopathological results obtained either by mediastinoscopy or thoracotomy in patients with clinically operable non-small cell lung cancer (NSCLC).Material and Methods This is a prospective, single-institution study of 68 consecutive patients with suspected or pathologically proven, localized, clinically resectable NSCLC (8 females and 60 males; mean age: 60.36 ±  1.01 years, range: 43–78 years). The patients underwent integrated PET/CT scanning at the same PET center. Standard cervical mediastinoscopy and extended mediastinoscopy were performed to sample the lymph nodes. During thoracotomy, complete mediastinal lymph node dissection was routinely performed.Results Mediastinoscopy gave true positive results in 9 patients and true negative results in 57 patients. There were two false negative results. Mediastinoscopy had a sensitivity of 81.8% (95% CI: 63–82), a specificity of 100% (95% CI: 96–100), a PPV of 100% (95% CI: 77–100), a NPV of 96.6% (95% CI: 93–96), and an accuracy of 97% for the detection of mediastinal lymph node metastases. When PET/CT results were compared with postoperative pathological examination results, PET/CT correctly identified 48 out of 50 patients (96%) who did not have metastatic lymph node involvement. N2/N3 disease was correctly determined by PET/CT in 8 of 11 patients (72.7%) who had positive results on histological analysis. When only N2 and N3 nodal diseases were included in the calculation with the aim of making a comparison with mediastinoscopy (for mediastinal nodes), integrated PET/CT had a sensitivity of 72.7% (95% CI: 51–80), a specificity of 97.7% (95% CI: 92–99), a PPV of 88.9% (95% CI: 62–97), a NPV of 93.3% (95% CI: 88–95) and an accuracy of 92.6% (95% 83–95) for the detection of intrathoracic N2 and N3 nodal metastases.Conclusion Our data shows that due to its high sensitivity and accuracy, mediastinoscopy is still the most reliable method to evaluate mediastinal lymph nodes in patients with NSCLC.
Keywords: mediastinoscopy; FDG PET/CT; lymph node; stage; non-small cell lung carcinoma; lung cancer treatment (surgery medical); lung cancer, diagnosis (includes staging imaging fiducials); mediastinum (incl. mediastinoscopy); positron emission tomography, PET